Animal- and management-based welfare indicators for a conventional broiler strain in 2 barn types (Louisiana barn and closed barn). (11th July 2018) - Louton, Helen; Bergmann, Shana; Reese, Sven; Erhard, Michael; Bachmeier, Josef; Rösler, Beatrice; Rauch, Elke
Abstract: The aim of this observational study was to describe health- and management-related welfare indicators for a conventional broiler strain housed in 2 barn types (Louisiana barn and closed barn) on the same farm and to assess the impact of age and housing conditions on these indicators. Broilers were examined 4 times in each of 7 fattening periods. Their weight gain, gait score, and further animal-based indicators did not differ between the barn types. On average 46% showed no sign, 51% a minor but visible, and 3% a profound lameness at the end of the fattening period (fattening day 39). Soiling of the plumage, skin scratches, foot pad dermatitis, and hock burns worsened with increasing age. Soiling of the plumage was correlated negatively with litter depth (Pearson, r = −0.549, P = 0.042) and positively with litter quality (Pearson, r = 0.641, P = 0.013). Skin scratches occurred in 89% of the broilers (32% deep with penetration of dermis) on fattening day 39 and were correlated positively with cumulative mortality (Pearson, r = 0.615, P = 0.019), indicating a severe animal welfare impact. Foot pad dermatitis did not correlate with health- or management-related indicators, whereas hock burn correlated positively with the broilers' weight (Pearson, r = 0.853, P < 0.001) and with ammonia concentrations (Pearson, r = 0.577, P = 0.031). Management-related indicators (antibiotic treatments, dead on arrival) and cumulative mortality did not differ between the barn types. At the end of the fattening period, the litter quality was worse and concentrations of ammonia and peaks of high carbon dioxide concentrations were higher in the Louisiana than in the closed barn. The light intensity was on average 20 times higher in the Louisiana than in the closed barn without any negative impact. Summarizing, the barn type did not seem to influence the investigated welfare indicators, but Louisiana barns might need a more precise management to maintain the required ranges of noxious gases and litter quality.